Executive function and attention-deficit/hyperactivity disorder in Ugandan children with perinatal HIV exposure. (8th May 2015) - Burkey, M. D.; Murray, S. M.; Bangirana, P.; Familiar, I.; Opoka, R. O.; Nakasujja, N.; Boivin, M.; Bass, J.K.
Abstract : Background: Attention-deficit/hyperactivity disorder (ADHD) is among the most commonly diagnosed mental disorders in childhood and is associated with substantial deficits in executive functioning and lost academic and occupational attainment. This study evaluates symptoms of ADHD and their association with neurocognitive deficits in a cohort of rural Ugandan children who were born to HIV-infected mothers. Methods: We assessed ADHD symptoms and executive function (including memory and attention) in a non-clinical sample of children born to HIV-infected mothers in rural eastern Uganda. Analyses included assessments of the psychometric properties, factor structure, and convergent and discriminant validity of the ADHD measure (ADHD-Rating Scale-IV); and executive function deficits in children meeting symptom criteria for ADHD. Results: 232 children [54% female; mean age 7.8 years (s.d. 2.0)] were assessed for ADHD and executive function deficits. The ADHD measure showed good internal consistency (α = 0.85.) Confirmatory factor analysis showed an acceptable fit for the diagnostic and statistical manual of mental disorders (DSM-5) two-factor model. Subjects meeting DSM-5 symptom criteria for ADHD had worse parent-rated executive function on six out of seven subscales. Conclusions: Our results demonstrate structural validity of the ADHD measure with this population, strong associations between ADHD symptom severity and poorer executive function, and higher levels of executive function problems in perinatally HIV-exposed Ugandan children with ADHD. These findings suggest that ADHD may be an important neurocognitive disorder associated with executive function problems among children in sub-Saharan African settings where perinatal HIV exposure is common.